Pornografi pada Remaja: Faktor Penyebab dan Dampaknya - Ramdhani, Muhammad Saufi; Asfari, Nur Amin Barokah (Flourishing Journal, 2022)
Abstract: Adolescence is the period between childhood and adulthood when significant changes occur in cognitive, physical, and emotional elements. During this time, there is a rise in interest in sexuality. Unfortunately, youngsters' sexual curiosity is not accompanied by adequate sex education. Most individuals still consider discussing sexuality to be taboo. Finally, teenagers tend to learn on their own, either by talking with friends or searching the internet. The ease with which adolescents can have access to the internet is one of the contributing elements that can lead to their becoming addicted to pornography.The amount of pornographic material available, as well as adverts including sexual content, remain visible on the device's screen. Using the literature study technique, this study attempts to investigate the causes and consequences of pornography addiction in adolescents. Pornography addiction in adolescents is induced by both internal and environmental influences, according to the findings. Curiosity, spirituality, and emotional factors are examples of internal factors. Pornography addiction in adolescents can impair cognitive, emotional, and social elements, as well as possibly unsafe sexual behavior, due to external causes such as easy access to pornographic material on the internet, peers, and a lack of sexual education. Abstrak: Memasuki masa remaja, terjadi perubahan signifikan terjadi pada elemen kognitif, fisik, dan emosional. Pada masa ini, terjadi peningkatan minat terhadap seksualitas. Sayangnya, keingintahuan seksual remaja tidak dibarengi dengan pendidikan seks yang memadai. Sebagian besar individu masih menganggap bahwa membicarakan seksualitas adalah hal yang tabu. Akhirnya, remaja cenderung belajar sendiri, baik dengan berbincang dengan teman atau mencari di internet. Salah satu faktor yang berkontribusi terhadap kecanduan pornografi pada anak-anak adalah kemudahan mereka mengakses internet. Banyaknya materi pornografi yang tersedia, serta iklan yang memuat konten seksual, tetap terlihat di layar gawai. Dengan menggunakan teknik studi literatur, penelitian ini mencoba untuk menyelidiki penyebab dan konsekuensi dari kecanduan pornografi pada remaja. Kecanduan pornografi pada remaja disebabkan oleh pengaruh internal dan lingkungan, menurut temuan. Keingintahuan, spiritualitas, dan faktor emosional adalah contoh faktor internal. Kecanduan pornografi pada remaja dapat merusak elemen kognitif, emosional, dan sosial, serta kemungkinan perilaku seksual yang tidak aman, karena penyebab eksternal seperti akses mudah ke materi pornografi di internet, teman sebaya, dan kurangnya pendidikan seksual.